Building on the shoulders of Bhaskar and Matthews: a critical realist criminology. Issue 2 (15th March 2022) - Wilkinson, Matthew; Quraishi, Muzammil; Irfan, Lamia; Schneuwly Purdie, Mallory
ABSTRACT: Building on the insights of the late Roy Bhaskar and the late Roger Matthews, as well as some recent developments in ultra-realist criminology, this article introduces and delineates some core intellectual contours of a Critical Realist Criminology (CRC) based on the principles of: The 'emergent, ' stratified ontology of crime and of the offender; the full critical realist account of the dialectics of being and becoming, including the spiritual turn in critical realism, applied to processes of criminal justice and reform; maximal inclusion of diverse theoretical research positions and the primacy of ontology in methodological selection; a 'serious' critical relationship of criminologists with professionals, institutions and policy-makers of criminal justice. These principles are directed at developing a criminology that 'underlabours' the recovery of human flourishing for the victims and perpetrators of crime and for society at large, including in-depth inquiry into what counts as crime and the purposes of incarceration.